The Lord's Supper Revisited: The Absence of Agape Context in the Lord’s Supper Today - Jessica (Asosiasi Teolog Indonesia, 2022)
The Lord’s Supper is probably one of the most vital elements in Christianity. However, churches nowadays witness two extreme attitudes in approaching the Lord’s Supper: one that over-sacralizes the ceremony as something mystical or magical while the other simply takes it as a ritual or memorial. While both notions are not wrong in some sense, the ceremony in fact falls somewhere in the middle. Eucharist involved two important dimensions: it is a meal, and it is a “sacrificial” meal. The ordinary and the religious aspects both exist within the eucharist. In the records of the Last Supper, Jesus ate the Passover “meal” with His disciples and reinstituted it. From then on, the early church celebrated the Lord’s Supper, gathering and breaking bread in houses, which was then known as agape—a love feast. However, what we witness in today’s Lord’s Supper is nowhere close to the original Last Supper or the early Christian agape feast. It becomes a ceremony without a meal; a celebration without a feast. It is ironic that the so-called “supper” only involves a wafer-like bread and a really small cup of wine. It is the absence of a “meal” that this ceremony becomes more and more detached. The Lord’s Supper becomes difficult to understand because of the emphasis on its sacredness. The ceremony remains a ritual as the “sacred” is separated from the “secular”. It is the contention of this study that the separation of the love feast from the ceremony of the Lord’s Supper that render it meaningless. This study aims to uncover the context and history of the Lord’s Supper, especially the significance of a feast or meal in the eucharist, and how it was lost in the course of history. We will see that it is in the context of a meal that the early church celebrates the eucharist, a thanksgiving in the form of a love feast. It is in the context of a meal that Jesus introduced His body and blood in the Last Supper. It is in the context of a meal that God commanded the Israelites to observe the Passover. When we approach the Lord’s Table without a proper meal, the eating of the “bread” and “wine” without context becomes a ritual without reality. Finally, suggestions are given to better approach the Lord’s Table, and hopefully regain the meaning and spirit of the ceremony.